METHODS OF EXPERIMENTAL RESEARCH JUSTIFICATION OF MINIMUM GEOMETRIC PARAMETERS OF GRAVEL BACKFILL IN THE OIL RECEIVER OF THE TRANSFORMER SUBSTATION: Array - Klуmas, R.; Nizhnуk, V.; Ballo, Ya.; Khromenkov, D.; Gulyk, Yu.; Ilchenko, N. (Municipal economy of cities. Series: «Economy science», 2021)
Transformer is one of the most fire-hazardous types of equipment at power substations. In case of emergency operation or damage to the integrity of the case they can cause a fire. Statistics on fires show that 50 % of fires in the energy sector are transformer equipment; as a rule, such fires are accompanied by an emergency spill of oil from the transformer and its ignition. Existing approaches to limiting the spread of fire during accidents at oil-filled transformer substations are insufficient and economically costly to minimize the consequences of burning transformer oil spills. At the same time, a number of design parameters have been identified that negatively affect the effectiveness of fire control. In particular, the Rules for Arrangement of Electrical Installations provide for the provision of electrical substations with oil receivers which is covered with gravel, and the latter is constantly polluted due to environmental influences which impairs its capacity and cooling capacity. The design and geometrical parameters of oil receivers with oil removal by oil drains defined in Rules for Arrangement of Electrical Installations can be a subject of scientific researches for their improvement. The purpose of this article is to determine the main provisions of the methodology of experimental studies to substantiate the minimum geometric parameters of gravel backfill in the oil receiver of the transformer substation. The ultimate goal of the study is to identify patterns of changes in the temperature of transformer oil from the parameters and characteristics of the oil pan, which should perform the function of a fire barrier and cooling the oil below the flash point. The essence of the method of experimental research is to identify patterns of reduction of the combustion temperature of transformer oil to a temperature below the flash point depending on the geometric parameters of the gravel backfill during oil draining into the emergency tank (oil tank). The developed technique allows to determine changes in the temperature of transformer oil from the geometric parameters of the oil pan, which should perform the function of a fire barrier and cooling the oil below the flash point.